Efforts to Improve Learning Outcomes by Using Simple Teaching Media Through Lesson Study Activities on General Physics Courses - Widyaningsih, Sri Wahyu; Yusuf, Irfan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
General Physics is one of the compulsory subjects not only for the Physics Education program but also for others including the Biology Education program. General Physics encompasses a wide range of materials that require a practicum. Unfortunately, not all laboratories could facilitate and had supporting tools for such practicum activities. It was believed that simple props can be used in learning activities especially to explain the concept of subject matter found in everyday life. This study aimed to determine the quality of General Physics learning by using simple media of learning in the Biology Education program, University of Papua. The research was conducted through the stages of Lesson Study activities namely Preparation Phase (Plan), Implementation (Do), and Reflection (See) in each cycle. The data was obtained through observation and video recordings during the learning activities. The results show that the quality of learning including the activities, cooperation, and mastery of the subject matter by the students are increasing in each cycle.